Condyloma acuminatum: some aspects - RIMKEVIČIUS, Arūnas; PŪRIENĖ, Alina; GAIGALAS, Mindaugas (Acta medica Lituanica, 2011)
Condyloma acuminatum is a rare human papilloma virus (HPV) related to oral lesion. The purpose of the article is to present a 42-year-old patient with condyloma acuminatum and to review references on the subject-related etiological, pathological, diagnostic and treatment aspects. Keywords: condyloma acuminatum, oral mucosa, papilloma virus, HIV